2022
DOI: 10.1096/fj.202200574r
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid‐stimulating hormone regulates cardiac function through modulating HCN2 via targeting microRNA ‐1a

Abstract: Previous studies have found microRNA‐1 (miR‐1) and hyperpolarization‐activated cyclic nucleotide‐gated channel 2 (HCN2) may be involved in the pathogenesis of thyroid hormone (TH) induced cardiac hypertrophy. However, little is known about the role of miR‐1 and HCN2 in thyroid stimulation hormone (TSH)‐induced cardiac dysfunction. In order to investigate the molecular mechanisms of TSH induced cardiac dysfunction and the role of miR‐1/HCN2 in that process, we evaluated the expression of miR‐1a/HCN2 in the vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…To our knowledge, no reports have been shown on these targets and warrant further investigation. Numerous studies have shown the vital roles of miRNAs in cardiovascular disorders [ 16 , 17 , 18 , 48 , 49 , 50 , 51 ]. In this study, we have also uncovered hundreds of significantly altered and novel miRNAs in TH-mediated cardiac regulation ( Supplementary File S7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no reports have been shown on these targets and warrant further investigation. Numerous studies have shown the vital roles of miRNAs in cardiovascular disorders [ 16 , 17 , 18 , 48 , 49 , 50 , 51 ]. In this study, we have also uncovered hundreds of significantly altered and novel miRNAs in TH-mediated cardiac regulation ( Supplementary File S7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown functional involvement of miRNAs in the heart associated with thyroid dysfunction [ 48 , 49 , 50 , 51 ]. A recent study from our group highlighted that the T3-induced protection from cardiac decompensation secondary to acute severe caloric restriction is partly mediated by lncRNAs [ 52 ].…”
Section: Introductionmentioning
confidence: 99%